Online Learning at English Study Program in State Polytechnic of Madiun - Imam Mudofir; Farid Maftuh; Alief Sutantohadi; Muhammad Supriyanto (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
The objectives of this study are 1) to find out the implementation of online learning model in English Study Program, State Polytechnic of Madiun, 2) to find out the obstacle factors in the implementation of online learning in English Study Program, State Polytechnic of Madiun, and 3) to know the supporting factors in the online learning process in English Study Program, State Polytechnic of Madiun. This research is a qualitative research with descriptive method. Analysis of research data obtained from the process of systematically searching and compiling, data obtained from observations, interviews, and documentation followed by data collection procedures, data reduction, data presentation, conclusions and verification, and checking the validity of the data (triangulation). The results of this study are 1) the implementation of online learning requires lesson plan, the effectiveness, efficiency and creativity of teachers in the online learning process, various applications in online learning, and an assessment in online learning. 2) Inhibiting factors in the implementation of online learning are communication saturation, limited interpersonal communication, limited space and time in learning activities, reduced student self-confidence, limited technology and information, the emergence of feelings of loneliness, limited media, online communication fatigue and limited media literacy, and student enthusiasm in participating in learning is still low. 3) The supporting factor in the online learning process is stable signal quality and adequate internet quota to support the success of online learning.